Quantitative Assessment of Ataxia in Multiple Sclerosis Patients using Spatiotemporal Parameters: A Relief-Based Machine Learning Analysis - Bilek, Furkan; Balgetir, Ferhat; Demir, Caner Feyzi; Alkan, Gokhan; Arslan-Tuncer, Seda (Georg Thieme Verlag Kg, 2021)
[Abstract Not Available]
Keywords: Multiple sclerosis; Ataxia; Machine learning; Relief method; Artificial neural networks